Navigation Model : More UX by transforming your system into a story - Manhaeve, Hendrik, ....- (Hendrik Manhaeve, 2021)
IT systems have a lot of functionality. We used to present this functionality as a whole to the user. He could then choose what he needed. This created enormous amounts of stress and many erroneous actions. It doesn’t have to be that way. A lot of stakeholder-oriented techniques may help you put the functionality in the right perspective for the user. The navigation model brings this information together and transforms it into a scenario, a narrative. Accompanied with the motivation of the user, we end up with a strong and stakeholder-oriented structure. The navigation model brings a lot of info together: the tasks, the environment, the business objects to be handled, the actions needed, the information to consult and last but not least why it is done that way, the motivation. The model draws a clear picture without using excessive details.
Keywords: Informatica; Ondernemen